ANALISIS PENGARUH PROFITABILITAS (ROE), STRUKTUR MODAL (DER), DAN KEPUTUSAN INVESTASI (PER) TERHADAP NILAI PERUSAHAAN (Studi pada Perusahaan Sektor Properti dan Real Estate yang Terdaftar di Bursa Efek Indonesia (BEI) Periode 2011-2014) - Singgih Kurnianto; Salamatun Asakdiyah (Jurnal Fokus Manajemen Bisnis, 2016)
This study aims to examine three independent variables Profitability (ROE), Capital Structure (DER) and Investment Decisions in predicts affect the dependent variable that is Company Value (Tobin's Q) in property and real estate companies listed on the Indonesia Stock Exchange (IDX) in the 2011-2014 period. This research method uses purposive sampling. Of the population of 40 companies that were sampled in the study were 26 companies. Tool the analysis used is linear regression analysis using the t test (partially) and the f test (simultaneously) using the SPSS program for windows version 20.0. The results of the t-test show that Retutn On Equity (ROE), Debt Equity Ratio (DER) and Price On Earning Ratio (PER) are all three significantly positive effect on Tobin's Q. From the results of the f test obtained the results that Retutn On Equity (ROE), Debt Equity Ratio (DER) and Price On Earning Ratio (PER) simultaneously influence Tobin's Q.